Techno-economics of Biochar and Biogas viability in Ghana (International Journal of Technology and Management Research, 2020)
Biogas and voucher are technological solutions that deal with sanitation and other environmental problems. The technology for producing biogas from faeces is termed bio-toilet and production of biochar from the same human waste is by means of Sol-char toilet. The study evaluated economic benefits and costs of sol-char toilet and compared with empirical benefits and costs estimates of bio-toilet. Cost Benefit Analysis was used to judge welfare change attribution of investment into Sol Char Toilet and Bio Toilet. The pyrolysis plant was fed with 4000 tons of faeces for which Sol char toilet incurred Total capital cost of US$ 3,140,940.38, Net Present Value (NPV) of US$9,718,817.4788, Profitability Index (PI) of 4.0942381271 and 1.4 years payback period. Bio toilet values for a total of 4000 m3 (100 units of 40 m3 each) were; - Total capital cost of US$ 36,026.05, NPV of US$89,152.75, PI of 3.4746 and 3.46 years payback period. Sol char toilet is faced with high capital requirement challenges, compared with an advantage in smaller payback period and a marginal difference in PI. The study concluded that complementary roles of sol char toilet and bio toilet in the Ghanaian economy is preferred.Keywords: Biogas; Biochar; Cost Benefit Analysis; Profitability Index; Payback period.